Incidence of Freshwater Aquatic Macrophytes in Relation to the Nutrients Content of Gwaigwaye and Mairuwa Reservoirs, Funtua, Nigeria - Lawal, N.,; Kuiwa, T.S.,; Jabbi, A.M.; Aminu, A.M. (UMYU Journal of Microbiology Research)
Studies were conducted between (September, 2017 to October, 2018) to investigate the variation in the compositional distribution of macrophyte communities in relation to the nutrient contents in the water and sediments of Mairuwa and Gwaigwaye reservoirs, Funtua located in the Northern vegetation of Nigeria. All the nutrients from sediments were analyzed using Standard procedures using Spectrophotometer, flame photometer and titration methods. Nitrogen, Phosphorus and Calcium were higher in Mairuwa reservoir than in Gwaigwaye; while Potassium on the other hand, was higher in Gwaigwaye than in Mairuwa reservoir. Magnesium was not detected in either of the two reservoirs. The modified method of flora collection was used with a random sampling technique. The correlation analysis indicated that the distribution and abundance of aquatic macrophyte composition were significantly (P<0.05) different. The overall community structure was made up of nine (9) from Mairuwa and eleven 11 species from Gwaigwaye reservoirs. Both the number of species present and the densities of such species were higher in Mairuwa than in Gwaigwaye reservoir. Four growth patterns of macrophytes were observed viz; Emergent macrophytes were the dominant (56.7%), Floating macrophytes (26.5%), submerged macrophytes (13.4%) and the least marginal macrophytes (3.4%). Similarly, species densities (stands per square metre) ranged from 1-29m, in Mairuwa, and 4-90m in Gwaigwaye. Implications of these trends to the well being of the two ecosytems are highlighted. Government and non-governmental organizations at all levels should ensure that the precious aquatic resources are solely protected by enacting laws against the anthropogenic action of the inhabitants in and around the catchment.